ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NASABAH MENABUNG: STUDI KASUS BANK SYARIAH DI SURABAYA - ARY YATIE, VIVIETA Ary (Jurnal Akuntansi AKUNESA, 2014)
Competition in Banking for attractcustomers candidate trigered in several element, one of those are growth from bank who can grown in people fund process. In addition to it, there are other several element that reputed to influence customers candidate for decide its banks choice too, that several element was product quality, system characteristic, and bank services. Analysis technique that used are double linier regresion and to test the hypotheses use t-test and F-test with 0,05 signification level. Based on research, found result that bank system characteristic and services had a positive influential and significant to customers decision to saving, mean while bank product quality doesn't had a positive and significant influential to customers decision to saving. To increase customers trust and loyalty to bank, bank it self must re-optimalized the product quality that offered to customers so that customer can get a satisfaction in case of using the bank service.Keyword: Customers decision to saving, product quality, system characteristic, and bank services.